Preventive medical right and its correlations with the deontology of health, education, good governance and compliance - De Souza Torres, Rogério (Seven Editora, 2023)
Deontology in health became an even more fashionable concern from 2005, after the edition of the Manual of Medical Ethics of the World Medical Association, which guided the mandatory study of Medical Ethics, Biotics and Rights through years in health sciences courses around the world, thus welcoming a curricular proposal that had been debated since the early 1980s. DOI: https://doi.org/10.56238/tfisdwv1-144